Comparison of Quality of Life in Twice Weekly versus Thrice Weekly Hemodialysis Populations: A single centre; cross sectional study - Salman, Ahmed; Nabi, Zahid; Rasheed, Humayun (Pakistan Journal of Kidney Diseases, 2024)
Abstract Hemodialysis is the preferable mode of treatment for more than 70% of patients with end-stage renal disease (ESRD). Variety of factors influence the QOL among hemodialysis population. Health-related quality of life (HRQOL) is a very important outcome for patients with end-stage renal disease (ESRD). The primary goal of healthcare initiatives is to provide quality care and concurrently rationalize costs. The primary objective of this study was to determine the frequency of adequate quality of life in patients on maintenance hemodialysis undergoing twice versus thrice weekly maintenance hemodialysis. Method: It was a cross-sectional study conducted over 6 months. HRQOL SF36 questionnaire was administered. Results: We found mean age of patients was 52.79±10.85 years with 53.7% patients were male and 46.3% patients were female. We also found adequate physical composite score in twice/week and thrice/week as (57.1% vs 39.3%, p=0.018), adequate mental composite score (70.3% vs 39.3%, p=0.0001) and adequate kidney disease component score (78.0% vs 57.1%, p=0.003). Twice/week patients showed better results in quality of life than thrice/week patients. Conclusion: We concluded that twice per week maintenance hemodialysis patients had better quality of life than thrice per week patients due to various factors.